Dynamics of catches and stocks of sprats of the Caspian Sea - V. P. Ivanov; L. A. Zykov (Юг России: экология, развитие, 2015)
The long-term data on stocks and cathing of the Caspian sprat are presented. The reasons of its dynamics are analyzed.